Consumer acceptance and willingness to pay for beef products derived from RNA interference technology - Britton, Logan Levi (Kansas State University, 2016)
Recent predictions estimate that the global population will reach more than 9 billion by the year 2050 (Kochhar, 2014). Coupled with this challenge, environmental issues and climate change influence agricultural production over the globe (Jacobsen et al., 2013). Changes in the food chain have been in response to consumers becoming interested in how their food is produced as it relates to food safety. Some of these changes have come in the form of labeling of production methods and the increasing volume of organic products in the marketplace. In the livestock sector, production methods include administration of antibiotics and hormones to prevent disease, increase gains and increase the health of animals (Allen et al., 2013; Thornton, 2010). A potential solution of decreasing the amount of antibiotics and hormones in the future is the use of ribonucleic acid interference (RNAi). RNA interference is a method of silencing a targeted gene and suppressing expression (Bradford et al., 2016). The focus of this research is to explore the determinants of acceptance and willingness to pay for beef products utilizing RNAi technology in the food system. Through the means of a national survey, consumers were asked their demographic, food purchasing habits, and food safety concerns to identify potential acceptors of the technology. Respondents received information treatments and external articles regarding RNAi technology as well as information about governmental labeling regulations of the beef steaks. Choice experiment questions, and a dichotomous choice sequence were utilized to determine willingness to pay estimates of beef steak attributes by consumers. Results showed that respondents likely require a discount for beef steaks produced with RNAi technology. In some instances, some consumers would be willing to pay a premium for beef steaks with RNAi in certain label settings. These results of this study could be used in the realm of animal science to help with the introduction of this technology in the food system. The survey results could assist with future promotion and framing of the technology to a wide variety of consumers.
Keywords: Consumer acceptance; Willingness to pay; Choice experiment; RNA interference; Information consumption